The Effect of Business Capital on Entrepreneurship Success with Self-Confidence as a Moderating Variable - Formaida Tambunan; Francisca Tiurma Damanik (RIRAI Publisher, 2023)
Business capital is a very important element for small industries to build their business to achieve success and self-confidence is also an important component in entrepreneurship. This study aims to determine the effect of business capital on entrepreneurial success moderated by self-confidence. The population in this study are all entrepreneurs in the area of Helvetia, Central Medan, as many as 121 entrepreneurs and samples are total. The data in this study consisted of primary data obtained through a questionnaire while secondary data was obtained through the Helvetia central village office was then processed and analyzed with simple regression analysis and MRA analysis. The results of the study show that 1) venture capital influences entrepreneurial success, and 2) venture capital influences entrepreneurial success moderated by self-confidence.